Research on the correlation between the processing technology of conjugated nanomaterials and the design of sports equipment - Miao, Yaguo (Frontiers in Chemistry, 2023)
The processing technology of conjugated nanomaterials and the design of sports equipment are often regarded as two independent fields, resulting in poor performance in sports equipment design. Analyze the characteristics, preparation methods, and potential applications of conjugated nanomaterials, and use the unique properties of conjugated nanomaterials to improve the performance of sports equipment. Graphene conducts electricity very well and is the hardest among nanomaterials. Carbon Nanotubes (CNTs) exhibit good thermal conductivity. Therefore, this paper proposes to use CNT and graphene materials in Natural Rubber (NR) composites in sports equipment, and explores the relationship between the two. The experimental results showed that after 1,200 cycles, the CNT capacitances of M-120//GO, M-160//GO, and M-180//GO reached 43.3%, 87.3%, and 46.5% of the initial specific capacitance, respectively, indicating that the electrochemical storage performance of M-160//GO capacitor is good and the stability is high. The application in sports equipment can improve the battery capacity and enhance the practicability of the equipment.